Modelling the potential spread of Hyalomma marginatum ticks in Europe by migratory birds. Issue 1 (January 2021) - Estrada-Peña, Agustín; D'Amico, Gianluca; Fernández-Ruiz, Natalia
Graphical abstract: Highlights: The routes of migratory birds (Africa-Europe) are modelled to capture the risk of introduction of H. marginatum immatures. The flight of birds into an area and thence the risk of introduction of H. marginatum in Europe is heterogeneous. The flyway going through western Europe-United Kingdom is one of the earliest that could introduce H. marginatum . The probability of introduction into Baltic and Nordic countries is still small. A warmer climate might support permanent populations of H. marginatum if a high number of immatures is introduced. Abstract: This study modelled the probability of introduction of Hyalomma marginatum into Europe by predicting the potential migratory routes of 28 bird species and the probability to carry immatures of the tick. Flyways were modelled as a spatio-temporal feature, at weekly intervals, using satellite-derived data of temperature and vegetal phenology, together with cost surfaces derived from speed and direction of the wind (years 2002–2018). The expected period of activity of tick immatures defined the probability of ticks being carried by birds along the modelled flyways. The probability of moulting of the engorged nymphs was modelled as a linear relationship of the daily sum of temperatures after tick introduction by birds. Positive probabilities of tick introduction extend the known northern range of permanent populations to central and western France, and large portions of central Europe. The flight of birds into an area and thence the risk of introduction of H. marginatum is very heterogeneous, with sites receiving "waves" of different bird species at diverse times of the year. Therefore, there is not a clear period of time for introduction, as it depends on the modelled behaviour of the bird species. The probability of introduction into Baltic and Nordic countries is small. We hypothesise that conditions of a warmer climate might support permanent populations of H. marginatum if a high number of immatures is introduced. Active surveys in risky territories, where the tick is not yet established, are advisable for rapid intervention.